Rules of Origin in ASEAN+1 Free Trade Agreements on Agriculture Commodity - Miranda Febriningtyas; Rina Oktaviani; Amzul Arifin (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2018)
Rules of origin that indirectly serve as trade barriers, thus raising the potential for increased production costs. In agricultural commodities, the rules of origin are primarily determined by wholly-obtained, so the potential for more significant increases in the cost of agricultural products versus other commodities. The purpose of this paper is to compare the restrictiveness index rules of origin in ASEAN + 1 FTAs (ACFTA, AJCEP, and AKFTA) on agricultural commodities. This study uses the Regime Wide Harris Index by Kelleher to calculate the restrictiveness level rules of origin in ASEAN + 1 FTAs. Based on product-specific regulations, AJCEP has the most flexible rules of origin, followed by AKFTA and ACFTA as the most restrictive of origin in ASEAN + 1 FTAs. In the Regime Wide Harris Index, the results show that AJCEP has a flexible origin rule after AKFTA, and ACFTA is the most strict rules of origin in ASEAN + 1 FTAs. These results are influenced by the most substantial diagonal side cumulation in the ACFTA.DOI: 10.15408/sjie/v7i1.6432